Fuzzy Control Fundamentals, Stability and Design of Fuzzy Controllers - Michels, Kai; Klawonn, Frank; Kruse, Rudolf; Nürnberger, Andreas (Studies in Fuzziness and Soft Computing, 2006)
The book provides a critical discussion of fuzzy controllers from the perspective of classical control theory. Special emphases are placed on topics that are of importance for industrial applications, like (self-) tuning of fuzzy controllers, optimisation and stability analysis. The book is written as a textbook for graduate students as well as a comprehensive reference book about fuzzy control for researchers and application engineers. Starting with a detailed introduction to fuzzy systems and control theory the reader is guided to up-to-date research results.